"Look at the Critique": Samba Schools and Carnival as Arenas of Protest and Rights Claims during Brazil’s Redemocratization (1980–1988) (Ágora Journal, 2025)
The article aims to analyze how Rio de Janeiro's samba schools used carnival as a critical platform and a means of advocating for rights during Brazil's re-democratization period (1980-1988). During this time, some associations engaged their themes, samba songs, and parades to turn them into vehicles of protest against the civil-military dictatorship, addressing issues such as repression, social inequality, and racism. Using primary and secondary sources, the research highlights how these schools redefined carnival, transforming it into a space for cultural resistance and citizenship. It concludes that the influence of samba musicians in constructing narratives of contestation reaffirmed the political role of carnival manifestations in Brazil’s historical context, thus aligning with a moment when the country was emerging from a repressive and exclusionary regime.
Keywords: Samba schools; Redemocratization; Civil-military dictatorship.